Pengaruh Earnings Management dan Tax Avoidance pada Nilai Perusahaan dengan Managerial Ownership sebagai Variabel Pemoderasi - Yunikayanti, Ni Komang; Wirajaya, I Gde Ary (Fakultas Ekonomi Universitas Samudra, 2025)
The research aims to analyze the influence of earnings management and tax avoidance on company value using managerial ownership as a moderating variable. This research method applies a quantitative approach in the form of an associative approach. This research was carried out on manufacturing sector companies listed on the IDX for the 2020-2022 period. A total sample of 111 observations was determined using the purposive sampling method, and analyzed using the moderated regression analysis (MRA) technique. The results show that earnings management and tax avoidance have a negative effect on company value, managerial ownership is unable to moderate the effect of earnings management on company value, and managerial ownership is unable to moderate the effect of tax avoidance on company value.